Políticas de fomento para micro e pequenas empresas: o Angola investe na ótica dos empresários - Simão, Lutumba Antônio Sebastião (2016)
The purpose of this dissertation was to study the development policies for microand small enterprises (SMEs) in Angola, specifically "Angola Investe", which is currently the main program for the promotion of MSEs in the country. The INAPEM. The theoretical reference points out important aspects of the country's economy,both in the colonial period and after independence. It defines the MPEs and the importance of policies to promote MSEs for the economy of Angola, in terms of economic diversification and incentive to national production and the implication of these companies in relation to inclusive development. The methodology used was qualitative exploratory character, because there were no studies on "Angola Investe" previously in the academy. The research subjects were micro and small entrepreneurs, from various sectors of the country's economy and specialists studying MSEs. The collection of data was of means of interviews and the analysis of the same was through analysis of categorial content. The results obtained by the research demonstrate that the program so far has not reached the established goals, although it is premature, to establish the success or failure of the same, it can be affirmed that there are some problems, that condition the best performance in the implementation Of the "Angola Investe". The joint analysis of data aligned with the logical model, an important tool for public policy analysis. The same model has shown that diversification of the economy and increasing national production are not yet a reality and that MSEs can be key elements for inclusive development. The conclusion was that there are problems inherent in the program and the economic market in Angola, which have a negative impact on the implementation of the program and we suggest the need for government policy modeling studies, the need to find an entity that is responsible for the financing , Routine studies of the profile of Angolan micro and small entrepreneurs, and ways of debureaucratizing the concession of licenses.